Increasing the Efficiency of Railway Transport by Improvement of Suspension of Freight Wagons - Dragan Petrović; Milan Bižić; Milomir Gašić; Mile Savković; Vladeta Gajić (Promet - Traffic&Transportation, 1970)
Railway transport has a very important role in economy of every country. The efficiency of railway transport depends both on the quality of transport organization and on the technical reliability of the railway rolling stock. During operation of the railway freight wagons in the last years, a large number of breaks of suspension system elements have been noticed. This feature is especially reported at four-axle double wagon for coal transport (designated Fbd) and three-axle wagon for transport of cars (designated DDam). Frequent breaks of suspension system elements reduce the efficiency of transport and in some cases cause derailment of wagons and lead to large economic losses. In this paper, the causes of breakage of suspension on both wagons (Fbd and DDam) have been analyzed, but also the possibilities of how to resolve these problems, i.e. how to reduce them to a minimum or avoid them completely.